1998
DOI: 10.1037/0022-3514.74.3.774
|View full text |Cite
|
Sign up to set email alerts
|

Self-control as a limited resource: Regulatory depletion patterns.

Abstract: If self-regulation conforms to an energy or strength model, then self-control should be impaired by prior exertion. In Study 1, trying to regulate one's emotional response to an upsetting movie was followed by a decrease in physical stamina. In Study 2, suppressing forbidden thoughts led to a subsequent tendency to give up quickly on unsolvable anagrams. In Study 3, suppressing thoughts impaired subsequent efforts to control the expression of amusement and enjoyment. In Study 4, autobiographical accounts of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

92
1,471
4
15

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,569 publications
(1,609 citation statements)
references
References 67 publications
92
1,471
4
15
Order By: Relevance
“…An experimenter approached participants and invited them to participate in a study investigating whether demographic factors are related to overall fitness levels among students. Following a procedure that Muraven et al (1998) developed, the experimenter took two handgrip measures of each participant, one before and one after the experimental manipulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An experimenter approached participants and invited them to participate in a study investigating whether demographic factors are related to overall fitness levels among students. Following a procedure that Muraven et al (1998) developed, the experimenter took two handgrip measures of each participant, one before and one after the experimental manipulation.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted this task from previous self-control studies, and it has been shown to require self-control (e.g., Muraven, Tice, & Baumeister, 1998). We further expected that happy participants with a mood management goal would perform no differently from control participants with a similar goal because both groups should be deterred from performing a task that is incongruent with the goal prime.…”
Section: Study 3: Physical Endurancementioning
confidence: 99%
“…Accumulating findings suggest that self-regulation operates on the basis of a limited resource that resembles a form of strength or energy. An early pair of investigations by Muraven, Tice, and Baumeister (1998) and Baumeister, Bratslavsky, Muraven, and Tice (1998) pitted three models of self-regulatory change against each other, using competing predictions as to what would happen on a second self-regulatory task as the result of having already performed a first self-regulatory task. First, a cognitive schema model might have predicted improvement on the second task as a result of priming the self-regulatory schema.…”
Section: Self-regulation As Strengthmentioning
confidence: 99%
“…Not surprisingly, ruminative, intrusive thoughts have been found to deplete people's cognitive resources, tax short-term memory (Krames & MacDonald, 1985), and impair their abilities to concentrate on task-relevant cognitions and behaviors (Martin & Tesser, 1989;Muraven, Tice, & Baumeister, 1998;Sarason, Sarason, Keefe, Hayes, & Shearin, 1986). For example, in a series of studies, dysphoric students induced to ruminate about themselves and their moods spent more time completing both important and trivial academic tasks and reported having more difficulty concentrating while performing those tasks than dysphoric students induced to distract themselves (Lyubomirsky, Kasri, & Zehm, 2003).…”
Section: What's So Bad About Dwelling?mentioning
confidence: 99%